Sejarah Peradilan Islam di Nusantara Masa Kesultanan-Kesultanan Islam Pra-Kolonial - Ismanto, Ismanto; Suparman, Suparman (Historia Madania: Jurnal Ilmu Sejarah, 2019)
What about the development of Islamic criminal law in Nusantara? This question should have been raised for the position of Islamic civil law is widely related to positive law, both as an influencing element or as a modification of religious norms formulated in civil law, even stated in the substantial legal scope of Law No.7 1989 dealing with religious justice. While Islamic law in the field of criminal justice - to mention another term of the Islamic criminal law - has not attracted much attention like the field of Islamic civil law. Apart from that, the available academic studies are often political in nature and broaden the distance between the understanding of positive criminal law and Islamic law in the field of criminal law. From a macro-historical perspective, the plurality of laws is inevitably a historical reality. The Positivism School believes that: the development of law is formalized for the sake of the law only. These circles strongly reject political interference in law, law by law, legal science in the form of value-free science while political science especially when associated with social science can be in the form of value-loaded science. According to this group's view, the procedure of finding, forming, and implementing law are in the hand of legal apparatus, the law can only be found through the judge's decision. The legal formation process is limited to legitimator products passed by the law. Law is a command of the law giver.